Analisis Kelayakan Ekonomi Investasi Pembangunan Embung Pulung Kencana di Kabupaten Tulang Bawang Barat - Elsa Permata Gusti; Ika Kustiani; Amril Ma'ruf Siregar (Jurusan Teknik Sipil Universitas Lampung, 2024)
Pulung Kencana Village is one of the villages located in West Tulang Bawang Regency. The location for the construction of the reservoir itself was planned on land that was not utilized optimally. The aim of this research was to determine the costs, benefits and investment feasibility value obtained from the construction of a reservoir in Pulung Kencana Village. This research is a case study that aired at analyzing the economic feasibility of investing in the construction of a reservoir based on the costs used and the economic benefits of the surrounding community from the construction of the Pulung Kencana Embung, Then the calculation of the costs and benefits will be processed to determine the feasibility of building the reservoir.The research data were analyzed using four methods, namely Net Present Value (NPV), Internal Rate of Return (IRR), Benefit Cost Ratio (BCR), and Payback Period (PP). The results of the analysis that the benefits of building embungs can be seen from three crucial sectors (agriculture, fisheries and tourism) and are considered feasible to continue to the next stage, because all scenarios meet the existing criteria. The best condition is in the eleventh scenario with calculations using an interest rate of 10% and the assumption that the annual income generated is 110%.